2022
DOI: 10.3390/diagnostics12030579
|View full text |Cite
|
Sign up to set email alerts
|

p53 Immunohistochemistry and Mutation Types Mismatching in High-Grade Serous Ovarian Cancer

Abstract: High-grade serous carcinoma (HGSCa) of the ovary is featured by TP53 gene mutation. Missense or nonsense mutation types accompany most cases of HGSCa that correlate well with immunohistochemical (IHC) staining results—an all (missense) or none (nonsense) pattern. However, some IHCs produce subclonal or mosaic patterns from which TP53 mutation types, including the wild type of the gene, cannot be clearly deduced. We analyzed a total of 236 cases of ovarian HGSCa and tumors of other histology by matching the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 30 publications
(28 reference statements)
0
15
0
Order By: Relevance
“… 60 , 61 However, several recent studies have reported a high frequency of p53 overexpression in tumors with TP53 nonsense mutations in the carboxyl terminus, as in the two cases in this study. 62 , 63 , 64 Although the mechanism of p53 overexpression in these cases has not been fully elucidated, it is possible that these mutations were not subject to nonsense‐medicated decay. 62 Moreover, the p53 oligomerization domain (amino acids: 325‐356) nonsense mutants could have received transcriptional feedback regulation.…”
Section: Discussionmentioning
confidence: 99%
“… 60 , 61 However, several recent studies have reported a high frequency of p53 overexpression in tumors with TP53 nonsense mutations in the carboxyl terminus, as in the two cases in this study. 62 , 63 , 64 Although the mechanism of p53 overexpression in these cases has not been fully elucidated, it is possible that these mutations were not subject to nonsense‐medicated decay. 62 Moreover, the p53 oligomerization domain (amino acids: 325‐356) nonsense mutants could have received transcriptional feedback regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Still, there is a lack of clinical, pathological, and epidemiological data on breast cancer subtypes and P53 immunoexpression [ 9 ]. P53 gene mutations are believed to be associated with 70% to 80% of triple-negative breast cancer cases (TNBC) [ 11 ]. In turn, triple-negative breast cancer represents about 12% to 20% of the breast cancer subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…2,14 Additionally, all three tumors showed aberrant expression of p53 IHC, which correlates with TP53 mutation. 17 Since conventional YSTs do not harbor TP53 mutation, 18 p53 IHC may be a helpful tool to differentiate somatically derived YST and conventional YST. 19 Previously, the frequency of YST-like differentiation in ovarian carcinomas had not been reported.…”
Section: Discussionmentioning
confidence: 99%